Samuel Beckett and communicational aesthetics: Between resonant worlds and material regimes - Yaltır, Selvin. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
While Samuel Beckett’s oeuvre manifests a wide array of communicational gestures, from voices and dialogues to more intricate webs of interrelation among bodies, affects, gestures, technological tools and voiceovers, communication has been a suspect term to define his work. This thesis examines Samuel Beckett’s work around an emergent idea of communication and works towards a definition of Beckettian aesthetics as “communicational.” It takes off from a nonstandard concept of communication that describes artistic creation, mainly derived from Deleuzean aesthetics, and proposes to analyze the various shifting conditions and material that make up Beckett's worlds of affection, perception, sensation and reflection. To that end, the chapters of this study discuss certain key texts and look at the ways in which diverse conditions, principles and topoi continually affect and resonate with each other across the oeuvre. By exploring the instances of a communicational gesture in the oeuvre, I seek to show that Beckett's language offers points of contact with affective, bodily, cognitive, social and political forms of expression. I suggest that considering the forms of sensibility and comprehensibility that Beckett's different levels of expression produce is significant to understanding his oeuvre-making. A novel understanding of communication in Beckett’s work contributes to the exploration of new forms of comprehensibility produced through implicit and provisional forms of knowledge across the oeuvre.